Hydrogen sulfide and its potential as a possible therapeutic agent in male reproduction - Pilsova, Zuzana; Pilsova, Aneta; Zelenkova, Natalie; Klusackova, Barbora; Chmelikova, Eva; Postlerova, Pavla; Sedmikova, Marketa (Frontiers in Endocrinology, 2024)
Hydrogen sulfide (H2S) is an endogenously produced signaling molecule that belongs to the group of gasotransmitters along with nitric oxide (NO) and carbon monoxide (CO). H2S plays a pivotal role in male reproductive processes. It is produced in various tissues and cells of the male reproductive system, including testicular tissue, Leydig and Sertoli cells, epididymis, seminal plasma, prostate, penile tissues, and sperm cells. This review aims to summarize the knowledge about the presence and effects of H2S in male reproductive tissues and outline possible therapeutic strategies in pathological conditions related to male fertility, e. g. spermatogenetic disorders and erectile dysfunction (ED). For instance, H2S supports spermatogenesis by maintaining the integrity of the blood-testicular barrier (BTB), stimulating testosterone production, and providing cytoprotective effects. In spermatozoa, H2S modulates sperm motility, promotes sperm maturation, capacitation, and acrosome reaction, and has significant cytoprotective effects. Given its vasorelaxant effects, it supports the erection of penile tissue. These findings suggest the importance and therapeutic potential of H2S in male reproduction, paving the way for further research and potential clinical applications.